ERIC VOEGELIN’S PHILOSOPHY OF HISTORY: Universal Humanity and the Tension of Historical Consciousness - Greenaway, James (Science et Esprit, 2023)
Eric Voegelin’s philosophy of history is both intellectually illuminating and evocative. It is also voluminous. Therefore, this essay selectively discusses some of the main themes of his mature thought. It begins with an exploration of what Voegelin found to be meaningful patterns in history. Then it elucidates the connection between his discovery of such patterns and the underlying theory of consciousness that he developed earlier, but which acted as a catalyst for his later thought. Voegelin’s concern to account for the emergence of historical consciousness was a key part of his philosophy of history, and is discussed here. Finally, the essay concludes with a brief meditation on the significance of his symbol, “universal humanity.”